Comparative Analysis of Pupil Diameters in Light and Dark Conditions After Instillation of 0.15% Brimonidine Drops in Eyes With and Without Pseudoexfoliation Syndrome - Sercan Cate; Çağlar Bektaş; Burak Turgut (Beyoglu Eye Journal, 2020)
INTRODUCTION[|] This study aimed to compare pupil diameters in light and dark conditions after instillation of 0.15% brimonidine drops in eyes with and without pseudoexfoliation syndrome (PES).[¤]METHODS[|]Forty eyes of 40 patients in whom 0.15% brimonidine drops were instilled to their right eyes between March 2019 and June 2019 were analyzed in this study. Study groups included 20 subjects without PES (group 1) and 20 patients with PES (group 2). Pupil diameters before and 30 and 90 min after brimonidine application were recorded and analyzed. [¤]RESULTS[|]In group 1, the mean pupil diameters before brimonidine drop instillation were 4.8+-1.2 mm and 5.8+-1.2 mm in light and dark conditions, respectively, while those in group 2 were 4.4+-1.2 mm and 4.9+-1.3 mm, respectively. At 30 min after brimonidine drop instillation, the pupil diameters in light and dark conditions were 4.3+-1.1 mm and 5.3+-1.0 mm in group 1 and 4.1+-1.1 mm and 4.5+-1 mm in group 2, respectively. In group 1, the mean pupil diameters at 90 min were 4.2+-1.1 mm and 5.1+-1.1 mm in light and dark, respectively, and in group 2, they were 4.0+-1.1 mm and 4.4+-1.2 mm, respectively. In the dark, the pupil diameters before drop instillation were significantly smaller in group 2 than in group 1 (p≤0.05). A significant difference was found between the groups with respect to the measurements in the dark at 30 min (p≤0.05). When the differences at 30 and 90 min and the initial pupil diameters in light condition were compared between the groups, the change in the pupil diameter at 30 min was statistically significant (p≤0.05). At 90 min, differences in both light and dark measurements were statistically significant (p≤0.05). [¤]DISCUSSION AND CONCLUSION[|]Brimonidine causes significant miosis in eyes with PES compared with eyes without PES. Brimonidine may have positive effects on spherical aberrations, glares, and halos. However, inadequate pupillary dilation may make it more difficult to perform cataract surgery and may further increase the complication rate. [¤]